Notification of Unexpected, Violent and Traumatic Death: A Systematic Review - De Leo, Diego; Zammarrelli, Josephine; Viecelli Giannotti, Andrea; Donna, Stefania; Bertini, Simone; Santini, Anna; Anile, Cristina (Frontiers in Psychology, 2020)
Background: The way the death of a dear person is communicated can have a profound impact on the entire bereavement process. The words and expressions that are used to give the tragic news, the characteristics of who communicates it, the physical setting in which the notification is given, the means used (e.g., in person, via phone call, etc.) are just some of the factors that can influence the way survivors face one of the most difficult moments in their lives. Aim: To review the literature on the topic of death notification to verify the state of the art related to this important procedure. Methods: A systematic review was conducted with PRISMA criteria on English-written materials produced from 1966 to 2019. Results: Out of the initial 3,166 titles considered, 65 articles were extracted for this review. Four main themes emerged: 1) protocols and guidelines; 2) emotional reactions of recipients and notifiers; 3) professional figures involved in the notification process; and, 4) types of death. Discussion: The communication of death represents a complex and stressful experience not only for those who receive it but also for those who give it. Alongside the acquisition of a necessary technique and execution methods, the process should involve the selection of notifiers based on personality characteristics and communication styles. Conclusion: Indications for the need of better training and protocols sensitive to different circumstances emerge. Adequate preparation can deeply affect the quality of communication and the effects it produces, both on recipients and on notifiers. In vocational training, more space should be devoted to this demanding task.